Differential Effect of Everolimus on Progression of Early and Late Cardiac Allograft Vasculopathy in Current Clinical Practice. Issue 5 (26th April 2013) - Masetti, M.; Potena, L.; Nardozza, M.; Prestinenzi, P.; Taglieri, N.; Saia, F.; Pece, V.; Magnani, G.; Fallani, F.; Coccolo, F.; Russo, A.; Rapezzi, C.; et al.
Abstract Randomized trials showed that mTOR inhibitors prevent early development of cardiac allograft vasculopathy (CAV). However, the action of these drugs on CAV late after transplant is controversial, and their effectiveness for CAV prevention in clinical practice is poorly explored. In this observational study we included 143 consecutive heart transplant recipients who underwent serial intravascular ultrasound (IVUS), receiving either everolimus or mycophenolate as adjunctive therapy to cyclosporine. Ninety‐one recipients comprised the early cohort, receiving IVUS at weeks 3–6 and year 1 after transplant, and 52 the late cohort, receiving IVUS at years 1 and 5 after transplant. Everolimus independently reduced the odds for early CAV (0.14 [0.01–0.77]; p = 0.02) but it did not appear to influence late CAV progression. High‐dose statins were found to be associated with reduced CAV progression both early and late after transplant (p ≤ 0.05). Metabolic abnormalities, such as high triglycerides, were associated with late, but not with early CAV progression. By highlighting a differential effect of everolimus and metabolic abnormalities on early and late changes of graft coronary morphology, this observational study supports the hypothesis that everolimus may be effective for CAV prevention but not for CAV treatment, and that risk factors intervene in a time‐dependent sequence during CAV development.